Investigations on container materials in high temperature microwave applications. (August 2017) - Behrend, Ralph; Dorn, Corina; Uhlig, Volker; Krause, Hartmut
Abstract: Microwave heating is a promising technology for high temperature materials processing, in particular melting of oxidic materials. The special characteristics of microwave heating and melting require refractory materials with very specific properties. The foremost important properties are microwave transparency, high thermal shock resistance as well as chemical and mechanical stability. This paper compares the suitability of some widely available refractory materials for use in microwave melting applications with a focus on boron nitride.